A bibliometric analysis of quality research papers in Islamic finance: evidence from Web of Science. Issue 1 (31st December 2020) - Tijjani, Bashir; Ashiq, Murtaza; Siddique, Nadeem; Khan, Muhammad Ajmal; Rasul, Aamir
Abstract : Purpose: The purpose of this study is to provide quantitative information on the growth of Islamic finance literature. The study focused on publishing trends, countries producing research on Islamic finance, key authors, major contributing organizations, authorship patterns, keywords and articles with the highest citations. Design/methodology/approach: Bibliometric analysis is applied to analyse the growth and publishing trends in Islamic finance literature. The Web of Science (WoS) database was used to extract bibliometric data covering the period 1939–2019 for Islamic finance literature. Findings: The study finds that Islamic finance research has gained remarkable momentum in the literature. However, such growth is largely manifested in Malaysia because of a conducive atmosphere for this type of research. Interestingly, the study finds that the three most productive journals are located in the UK and Malaysia, while Professor M. Kabir Hassan from the University of New Orleans, the USA appears to head the list of authors with 23 publications on Islamic finance. Practical implications: This study provides up-to-date literature on the current state of Islamic finance in the world; as a result, it supports the development of policies by the Islamic finance industry. The findings of the study also serve as a reference point for Islamic finance training and educational institutions. Originality/value: Islamic finance is an emerging financial discipline; as such, there is a need for more awareness of this financial system in the world. Muslim-majority countries, especially Saudi Arabia, Turkey, Indonesia, the United Arab Emirates (UAE), Pakistan and Bahrain, have to include Islamic finance in their curriculum and establish research institutions and research journals. In addition, Arabic language journals should be indexed in WoS and/or Scopus to provide a high-quality publication platform. This study provides a more comprehensive bibliometric analysis on the growth of Islamic finance literature (1939–2019) in the WoS database; most of the prior studies have covered relatively few areas of focus and a lower range of years in some cases.